Patterns of Alcohol Consumption in Spanish University Alumni: Nine Years of Follow-Up - Gómez, Patricia; Moure-Rodríguez, Lucía; López-Caneda, Eduardo; Rial, Antonio; Cadaveira, Fernando; Caamaño-Isorna, Francisco (Frontiers in Psychology, 2017)
The aim of this study was to empirically identify different profiles of Spanish university alumni, based on their alcohol use over nine years, and to further characterize them. A cohort study was carried out between 2005 and 2015 among university students (Compostela Cohort-Spain; n2015 = 415). Alcohol consumption was measured using the Alcohol Use Disorder Identification Test (AUDIT). A two-stage cluster analysis, based on their AUDIT total scores was carried out separately for males and females. The further characterization of every profile was based on demographic data, age at onset of alcohol use, positive alcohol-related expectancies, tobacco and cannabis use, as well as their answers to some European Addiction Severity Index items. Five different clusters were identified: Low users (29.2%), Moderated users (37.2%), At-risk users (14.2%), Decreasing users (13.2%) and Large users (6.2%) for females, and Low users (34.4%), At-risk users (25.6%), High-risk users (15.6%), Decreasing users (14.4%) and Large users (10.0%) for males. Being a cannabis user or a smoker was positively associated to those more hazardous clusters in both genders. Regarding females, significant differences in the age of onset and high positive expectancies were found. However, there were few significant differences among the groups in relation to their employment status and social relations. The results reveal the existence of different typologies of alcohol users among university alumni, with differences among males and females. Modifying positive expectancies, limiting access to alcohol at a young age, and reducing uses of other substances uses are key to promote healthier alcohol use profiles and to prevent hazardous uses.